Eksplorasi Wisata Kuliner - Studi Kasus Di Bali - Vishnuvardhana S. Soeprapto; Elva Yohana (Akademi Pariwisata Bunda Mulia, 2021)
Indonesia has various destinations that are also rich in culinary delights. This research is to see the various factors that influence tourists in choosing destinations for culinary tourism destinations. The focus of the destination is the island of Bali. Bali is a most famous destination not only in Indonesia but also abroad. We will see if the purpose of going to Bali is to experience culinary delights and make Bali a destination for culinary delights. This research is a descriptive and exploratory study